Digital Maturity in Vocational Secondary Schools (SMK) - Yarmanto, Edhy Sri; Setiawan, Agus; Kustiawan, Iwan (Journal of Vocational Education Studies, 2025)
Digital transformation has taken place in various sectors of life, and has also penetrated into Vocational Secondary Schools (SMK). Research on digital maturity in vocational schools is still rare. The purpose of this study is to develop a digital maturity model that includes the dimensions and the level of digital maturity, digital maturity measurement instruments, and to measure digital maturity in vocational schools. The instrument developed has met the validity and reliability test and can be used for quantitative research on digital maturity measurement. The dimensions of digital maturity include: management and organization, people and culture, products and services, technology, and organizational operations. Meanwhile, the maturity level consists of 5 levels: not ready, initial readiness, intermediate readiness, mature readiness, and already implemented. The measurement results showed that the vocational school that was the subject of the study was in mature readiness. This study concludes that digital transformation in vocational schools is a necessity. The resulting assessment models and instruments can be used to measure digital maturity in vocational schools. This study was conducted at a vocational school, which opened up space for future study. The form of research can deepen the dimension of digital maturity, or research for high schools, both public or private high schools.